The Effectiveness of Communication by Members of the Medan City Council in Absorbing the Aspirations of the Community in Electoral District I of Medan Helvetia Subdistrict - Saurma MGP Siahaan; Mega Ulva Sari Sihombing; Rachel Mia Lorenza Lumban Toruan; Dasmauli Purba (Universitas Dharmawangsa Medan, 2025)
This research aims to determine and analyze the effectiveness of the recess communication of the Medan City DPRD Members in Medan Helvetia District, as well as identifying supporting and inhibiting factors. The background of this research is based on the Performance Report of the Medan City DPRD which shows that there are still many basic needs and general needs of the community that require attention. The research method uses a descriptive qualitative approach with in -depth interview techniques and observations. The results showed that recess communication took place quite effectively, marked by the direct involvement of DPRD members, the delivery of clear information, and active participation of the community. Supporting factors include the communication media used, the selection of appropriate time, and openness to receive input. The obstacle found is the inaccuracy of the implementation time in several locations. Overall, recess activities are a means of two -way communication that builds closeness and public trust, but requires an increase in time discipline and strengthening the follow -up of aspirations so that the absorption of aspirations is more optimal.